Author Correction: A semi-automated virtual workflow solution for the design and production of intraoral molding plates using additive manufacturing: the first clinical results of a pilot-study (Scientific Reports, (2018), 8, 1, (11845), 10.1038/s41598-018-29959-6) - Grill, Florian D.; Ritschl, Lucas M.; Bauer, Franz X.; Rau, Andrea; Gau, Dominik; Roth, Maximilian; Eblenkamp, Markus; Wolff, Klaus Dietrich; Loeffelbein, Denys J. (Scientific Reports, 2020)
This Article contains errors in Table 2 where the two columns headings have been reversed. ‘CAD/CAM NAM’ and ‘RapidNAM’ should read ‘RapidNAM’ and ‘CAD/CAM NAM’ respectively.
CRIS-Team Scopus Importer:2020-03-27